Increasing Junior High School Students' Mathematical Comprehension with Realistic Mathematics Education (RME) Approach - Ukhti Agus Setyawati; Naning Kurniawati; Festian Cindar Bumi (Universitas Islam Sultan Agung, 2022)
Mathematical understanding is an important basis for thinking whensolving mathematical problems. Mathematical understanding is also the basis ofthinking in learning mathematics to find out the results of mastery learning. Thiscan be seen in the results of the test scores of students with mathematicalunderstanding abilities that are still below the level of mastery learning, thereforethe importance of mathematical understanding abilities is increased by using theRealistic Mathematical Education (RME) learning approach. This study uses mixedmethods where the research strategy combines qualitative and quantitative methodssimultaneously. The results of the research conducted the average score was stilllow, namely 62.5% below the average and 37.5% above the average, but afterapplying the RME learning method, it showed that the average student scoreincreased to 21.9 % below average and 78.1% above average. Based on the resultsbefore and after the test, students' mathematical understanding ability increased by40.6% after applying the RME teaching method, thus proving that RME had apositive effect on increasing mathematical understanding.